Intensity-modulated radiotherapy versus stereotactic body radiotherapy for prostate cancer (PACE-B): 2-year toxicity results from an open-label, randomised, phase 3, non-inferiority trial. Issue 10 (October 2022) - Tree, Alison C; Ostler, Peter; van der Voet, Hans; Chu, William; Loblaw, Andrew; Ford, Daniel; Tolan, Shaun; Jain, Suneil; Martin, Alexander; Staffurth, John; Armstrong, John; Camilleri, Philip; et al.
Summary: Background: Localised prostate cancer is commonly treated with external beam radiotherapy and moderate hypofractionation is non-inferior to longer schedules. Stereotactic body radiotherapy (SBRT) allows shorter treatment courses without impacting acute toxicity. We report 2-year toxicity findings from PACE-B, a randomised trial of conventionally fractionated or moderately hypofractionated radiotherapy versus SBRT. Methods: PACE is an open-label, multicohort, randomised, controlled, phase 3 trial conducted at 35 hospitals in the UK, Ireland, and Canada. In PACE-B, men aged 18 years and older with a WHO performance status 0–2 and low-risk or intermediate-risk histologically-confirmed prostate adenocarcinoma (Gleason 4 + 3 excluded) were randomly allocated (1:1) by computerised central randomisation with permuted blocks (size four and six), stratified by centre and risk group to control radiotherapy (CRT; 78 Gy in 39 fractions over 7·8 weeks or, following protocol amendment on March 24, 2016, 62 Gy in 20 fractions over 4 weeks) or SBRT (36·25 Gy in five fractions over 1–2 weeks). Androgen deprivation was not permitted. Co-primary outcomes for this toxicity analysis were Radiation Therapy Oncology Group (RTOG) grade 2 or worse gastrointestinal and genitourinary toxicity at 24 months after radiotherapy. Analysis was by treatment received and included all patients with at least one fraction of study treatment assessed for late toxicity. Recruitment is complete. Follow-up for oncological outcomes continues. The trial is registered with ClinicalTrials.gov, NCT01584258 . Findings: We enrolled and randomly assigned 874 men between Aug 7, 2012, and Jan 4, 2018 (441 to CRT and 433 to SBRT). In this analysis, 430 patients were analysed in the CRT group and 414 in the SBRT group; a total of 844 (97%) of 874 randomly assigned patients. At 24 months, RTOG grade 2 or worse genitourinary toxicity was seen in eight (2%) of 381 participants assigned to CRT and 13 (3%) of 384 participants assigned to SBRT (absolute difference 1·3% [95% CI –1·3 to 4·0]; p=0·39); RTOG grade 2 or worse gastrointestinal toxicity was seen in 11 (3%) of 382 participants in the CRT group versus six (2%) of 384 participants in the SBRT group (absolute difference –1·3% [95% CI –3·9 to 1·1]; p=0·32). No serious adverse events (defined as RTOG grade 4 or worse) or treatment-related deaths were reported within the analysis timeframe. Interpretation: In the PACE-B trial, 2-year RTOG toxicity rates were similar for five fraction SBRT and conventional schedules of radiotherapy. Prostate SBRT was found to be safe and associated with low rates of side-effects. Biochemical outcomes are awaited. Funding: Accuray.